PERAN KEPEMIMPINAN KEPALA SEKOLAH PADA IMPLEMENTASI STANDAR PROSES PEMBELAJARAN PENDIDIKAN DASAR - Andarwati, Ayu Setia; Shiddiq, Ngarifin; Haryanto, Sri (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2022)
Primary education aims to lay the foundation of intelligence, knowledge, personality, noble character, and skills for independent living. Resources as the output of the educational process are required to produce intellectually and spiritually intelligent human help. Islamic-based Basic Education is one of the Educational Institutions with a vision of building spiritual intelligence and intellectual intelligence. Islamic-based school leadership has a very central role. This is stated in Surah Al-Anbiya’ chapter 73: "And We made them as leaders who guide with Our orders..." Changes in the learning process due to changes and developments in information technology become challenges, opportunities, innovations, and leadership roles to realize the school's vision. Principal leadership has the function of controlling and developing the learning process by applicable process standards. The research question is what is the role of leadership by Surat Al-Anbiya’ verse 73, and how is the implementation of the part in carrying out standard learning processes in Islamic-based elementary schools? This study aims to obtain a description of the leadership concept relevant to Surah Al-Anbiya’ verse 73 and produce a report on the leadership role of Islamic-based elementary school principals in implementing educational standards. This research was conducted at SD MBF Al-Adzkiya and SD Al-Madina Wonosobo. The determination of the research object is based on the Vision and Mission as well as the characteristics of the process of implementing education in Islamic-based schools in Wonosobo. The benefit of this research is to produce a leadership concept model for Basic Education (elementary school level), which is based on Surah Al-Anbiya’ verse 73, as well as a descriptive description of the implementation process of implementing education in Islamic-based schools in Wonosobo.